STRENGTHENING ORGANIZATIONAL CULTURE, TRANSFORMATIONAL LEADERSHIP, AND PERSONALITY IN EFFORTS TO IMPROVE TEACHER PERFORMANCE: Empirical Study Using Correlation Approach and Sitorem Analysis on Elementary School Teachers in Jakarta Barat City - Tajudin, Tajudin; Setyaningsih, Sri; Sunaryo, Widodo (International Journal of Social and Management Studies, 2021)
In the world of education, teachers have a very large and important role in teaching and learning activities because teachers are educators who are directly related to students, so teachers are required to have good performance in order to teach students who have good quality as well. One of the educational problems faced by the Indonesian people is the low quality of education at every level and unit of education, especially primary and secondary education. Various efforts have been made to improve the quality of education, among others through various training and improvement of teacher qualifications, procurement of books and learning tools, improvement of facilities and infrastructure, and improvement of the quality of school management. However, various indicators for improving the quality of education have not shown an even increase. Based on preliminary research, it is known that the performance of SDN teachers in West Jakarta City has a teacher performance problem, namely that teacher performance has not been achieved in accordance with the target, therefore research is needed to obtain information on variables related to teacher performance.This study aims to find efforts to overcome teacher performance problems by knowing the strength of the variables that are thought to affect teacher performance. In this case, it is the organizational culture, transformational leadership and personality and together with the related variables, namely teacher performance. The research population consisted of all teachers from elementary schools in Jakarta Barat City. The sampling technique used Multistage Proportional Random Sampling, and the Slovin formula was used to determine the number of samples in order to obtain 589 samples. The results of the study found that all variables had a significant positive relationship with teacher performance towards the organization, in order based on the strength of the relationship as follows: organizational culture (ry1 = 0.996, ρ <0.05), transformational leadership (ry2 = 0.976, ρ <0, 05), and personality (ry3 = 0.993, ρ <0.05).The results of the SITOREM analysis show that the components of teacher performance that have priority improvements that need to be improved are: (1) Stable, Implementation of the concept of teacher performance related to quality in the implementation of learning, (2) Quantity, Implementation of Teacher Performance Concepts specifically related to Quantity in the implementation of learning, (3 ) Innovation, Implementation of Teacher Performance Concepts specifically related to Quality in implementation in learning, (4) Agreeableness, Implementation of Teacher Performance Concepts specifically related to Quality in implementation in learning. The suggestions that can be submitted for principals and teachers are to maintain indicators that have a fairly good score.